2023
DOI: 10.3389/fimmu.2023.1155377
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with methotrexate nanoconjugate and dendritic cells with downregulated IL-10R expression modulates the tumor microenvironment and enhances the systemic anti-tumor immune response in MC38 murine colon carcinoma

Abstract: BackgroundUnderstanding the negative impact of the tumor microenvironment on the creation of an effective immune response has contributed to the development of new therapeutic anti-cancer strategies. One such solution is combined therapy consisting of chemotherapeutic administration followed by dendritic cell (DC)-based vaccines. The use of cytostatic leads to the elimination of cancer cells, but can also modulate the tumor milieu. Moreover, great efforts are being made to increase the therapeutic outcome of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
(76 reference statements)
2
7
0
Order By: Relevance
“…However, given that the observed increases in DC abundance intratumorally and from BM-derived DCs are comparable, we are confident that the findings from bmDCs would translate to intratumor DCs. Additionally, bmDCs have previously been used to deduce specific aspects of DC biology using similar culturing conditions to that of this study (109)(110)(111)(112)(113), further supporting the validity of this methodology. Interestingly, through our in vivo and ex vivo studies we observed that L-fuc increases cDC1 and moDC abundance in similar proportions.…”
Section: Discussionsupporting
confidence: 69%
“…However, given that the observed increases in DC abundance intratumorally and from BM-derived DCs are comparable, we are confident that the findings from bmDCs would translate to intratumor DCs. Additionally, bmDCs have previously been used to deduce specific aspects of DC biology using similar culturing conditions to that of this study (109)(110)(111)(112)(113), further supporting the validity of this methodology. Interestingly, through our in vivo and ex vivo studies we observed that L-fuc increases cDC1 and moDC abundance in similar proportions.…”
Section: Discussionsupporting
confidence: 69%
“…DAMPs excreted by dying cells can initiate an immune response, followed by the maturation of the antigen-presenting DCs. However, the immunosuppressive TME hinders the anticancer immune response triggered by DCs ( 43 ). MDSCs, Tregs and tumor cells secrete suppressive cytokines, that can inhibit CTLs ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of conjugation of a low-molecular-weight drug with a high-molecularweight carrier provides an optimal hydrodynamic diameter of the obtained HES-MTX nanoconjugate. This enables more efficient accumulation in tumor tissue, mainly through enhanced vascular permeability and retention effect (EPR), which was discussed in more detail in our previous publication (12). Moreover, the anticancer activity of HES-MTX has been confirmed in murine and human leukemia models (10), as well in the murine colon carcinoma MC38 model (12,13).…”
Section: Introductionmentioning
confidence: 88%
“…This enables more efficient accumulation in tumor tissue, mainly through enhanced vascular permeability and retention effect (EPR), which was discussed in more detail in our previous publication ( 12 ). Moreover, the anticancer activity of HES-MTX has been confirmed in murine and human leukemia models ( 10 ), as well in the murine colon carcinoma MC38 model ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation